Periodicity Pitch Perception - Klefenz, Frank; Harczos, Tamas (Frontiers in Neuroscience, 2020)
This study presents a computational model to reproduce the biological dynamics of "listening to music". A biologically plausible model of periodicity pitch detection is proposed and simulated. Periodicity pitch is computed across a range of the auditory spectrum. Periodicity pitch is detected from subsets of activated auditory nerve fibers (ANFs). These activate connected model octopus cells, which trigger model neurons detecting onsets and offsets, thence model interval-tuned neurons are innervated at the right interval times, and finally a set of common interval detecting neurons indicate pitch. Octopus cells rhythmically spike with the pitch periodicity of the sound. Batteries of interval-tuned neurons stopwatch-like measure the inter-spike intervals of the octopus cells by coding interval durations as first spike latencies (FSLs). The FSL triggered spikes synchronously coincide through a monolayer spiking neural network at the corresponding receiver pitch neurons.